The Chaperone and Redox Properties of CnoX Chaperedoxins Are Tailored to the Proteostatic Needs of Bacterial Species - Camille V. Goemans (American Society for Microbiology, 2018)
ABSTRACT Hypochlorous acid (bleach), an oxidizing compound produced by neutrophils, turns the Escherichia coli chaperedoxin CnoX into a powerful holdase protecting its substrates from bleach-induced aggregation. CnoX is well conserved in bacteria, even in non-infectious species unlikely to encounter this oxidant, muddying the role of CnoX in these organisms. Here, we found that CnoX in the non-pathogenic aquatic bacterium Caulobacter crescentus functions as a holdase that efficiently protects 50 proteins from heat-induced aggregation. Remarkably, the chaperone activity of Caulobacter CnoX is constitutive. Like E. coli CnoX, Caulobacter CnoX transfers its substrates to DnaK/J/GrpE and GroEL/ES for refolding, indicating conservation of cooperation with GroEL/ES. Interestingly, Caulobacter CnoX exhibits thioredoxin oxidoreductase activity, by which it controls the redox state of 90 proteins. This function, which E. coli CnoX lacks, is likely welcome in a bacterium poorly equipped with antioxidant defenses. Thus, the redox and chaperone properties of CnoX chaperedoxins were fine-tuned during evolution to adapt these proteins to the specific needs of each species. IMPORTANCE How proteins are protected from stress-induced aggregation is a crucial question in biology and a long-standing mystery. While a long series of landmark studies have provided important contributions to our current understanding of the proteostasis network, key fundamental questions remain unsolved. In this study, we show that the intrinsic features of the chaperedoxin CnoX, a folding factor that combines chaperone and redox protective function, have been tailored during evolution to fit to the specific needs of their host. Whereas Escherichia coli CnoX needs to be activated by bleach, a powerful oxidant produced by our immune system, its counterpart in Caulobacter crescentus, a bacterium living in bleach-free environments, is a constitutive chaperone. In addition, the redox properties of E. coli and C. crescentus CnoX also differ to best contribute to their respective cellular redox homeostasis. This work demonstrates how proteins from the same family have evolved to meet the needs of their hosts.